Investigation of Grid-Tied Photovoltaic Power Plant on Medium-Voltage Feeder: Palestine Polytechnic University Case Study - Maher Maghalseh; Nassim Iqteit; Haitham Alqadi; Salman Ajib (Solar)
The conventional unidirectional power flow model of centralized energy grids is being revolutionized by integrating renewable energy sources, particularly photovoltaic (PV) systems, to meet the escalating demand for electricity while ensuring sustainability. However, this integration challenges the efficiency and performance of power systems and impacts various parameters, including power quality, voltage profile, power factor, power loss, and load flow. This paper investigates the effects and performance of a grid-tied PV system integrated into the conventional power system, focusing on the Palestine Polytechnic University (PPU) 230 kWp PV plant as a real-world case study. Simulations conducted using ETAP software revealed that integrating the PV system resulted in a slight increase in the voltage level at the main bus of the PPU feeder, with an increase of 0.03% at the medium-voltage level. Additionally, the voltage level at the Point of Common Coupling (PCC) increased by 0.51% with a PV penetration level of only 14.7%, which remains within the acceptable range according to IEEE 1547 standards. These findings underscore the minimal impact of the PV system on the voltage profile and highlight the system’s ability to maintain power quality and efficiency even with the addition of renewable energy sources. The daily load profiles were studied with and without the PV system, providing a comprehensive analysis of its effects on the grid.